MENINGKATKAN KEMAMPUAN KONEKSI MATEMATIS SISWA MELALUI STRATEGI BELAJAR PREVIEW QUESTION READ REFLECT RECITE REVIEW - Roslani Supinah; Kadir Kadir; Otong Suhyanto (Faculty of Educational sciences, UIN Syarif Hidayatullah Jakarta, 2020)
The PQ4R (Preview, Question, Read, Reflect, Recite, Review) learning strategy is one of the recommended learning strategies to hone mathematical connection skills and support students to connect mathematical concepts with problems in everyday life. The purpose of this study was to examine the effect of PQ4R learning strategies and conventional learning strategies on students' mathematical connection abilities. This study was a quasi-experimental study with a two group randomized control group post test only design. This study involved 60 students who were taken randomly as samples, 30 students each for the experimental and control groups. Data collection using test instruments. The research findings reveal that the average mathematical connection ability of the experimental group is 71.53 and the control group is 35.99. The achievement of mathematical connection ability includes connection indicators: between mathematics, with other disciplines, and with everyday life. The conclusion of this study is that the PQ4R learning strategy is more effective in increasing the mathematical connection ability than students who are given conventional learning strategies.